The plastidial protein acetyltransferase GNAT1 forms a complex with GNAT2, yet their interaction is dispensable for state transitions - Brünje, Annika; Füßl, Magdalena; Eirich, Jürgen; Boyer, Jean-Baptiste; Heinkow, Paulina; Neumann, Ulla; Konert, Minna; Ivanauskaite, Aiste; Seidel, Julian; Ozawa, Shin-Ichiro; Sakamoto, Wataru; Meinnel, Thierry; et al. (Elsevier BV, 2025)
Protein N-acetylation is one of the most abundant co- and post-translational modifications in eukaryotes, extending its occurrence to chloroplasts within vascular plants. Recently, a novel plastidial enzyme family comprising eight acetyltransferases that exhibit dual lysine and N-terminus acetylation activities was unveiled in Arabidopsis. Among these, GNAT1, GNAT2, and GNAT3 reveal notable phylogenetic proximity, forming a subgroup termed NAA90. Our study focused on characterizing GNAT1, closely related to the state transition acetyltransferase GNAT2. In contrast to GNAT2, GNAT1 did not prove essential for state transitions and displayed no discernible phenotypic difference compared to the wild type under high light conditions, while gnat2 mutants were severely affected. However, gnat1 mutants exhibited a tighter packing of the thylakoid membranes akin to gnat2 mutants. In vitro studies with recombinant GNAT1 demonstrated robust N-terminus acetylation activity on synthetic substrate peptides. This activity was confirmed in vivo through N-terminal acetylome profiling in two independent gnat1 knockout lines. This attributed several acetylation sites on plastidial proteins to GNAT1, reflecting a subset of GNAT2's substrate spectrum. Moreover, co-immunoprecipitation coupled to mass spectrometry revealed a robust interaction between GNAT1 and GNAT2, as well as a significant association of GNAT2 with GNAT3 - the third acetyltransferase within the NAA90 subfamily. This study unveils the existence of at least two acetyltransferase complexes within chloroplasts, whereby complex formation might have a critical effect on the fine-tuning of the overall acetyltransferase activities. These findings introduce a novel layer of regulation in acetylation-dependent adjustments in plastidial metabolism.